Breast is Best, but Where? Hostile Sexism Underlies Men's Opposition to Breastfeeding in Public. (15th June 2020) - Huang, Yanshu; Sibley, Chris G.; Osborne, Danny
Abstract: Breastfeeding in public remains controversial in many Western nations. Prior work reveals that restrictive gender role attitudes and hostility toward women's empowerment contribute to the policing of women's bodies, especially when it comes to breastfeeding in public. Using a national sample of New Zealand adults ( N = 16, 789), we investigated the relationships of hostile and benevolent sexism with attitudes toward breastfeeding in public, as well as the potential moderating effects of gender. Results revealed that, although benevolent sexism only positively correlated with opposition to public breastfeeding for women, hostile sexism correlated positively with opposition to public breastfeeding among both women and men. These results suggest that opposition to breastfeeding in public is primarily rooted in hostile attitudes toward women who are perceived as violating traditional gender roles. Accordingly, social and health policies including information campaigns that reduce hostilely sexist stigmas of breastfeeding in public could help promote women's breastfeeding autonomy.